2019
DOI: 10.7759/cureus.5634
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring Versus Self-Monitoring of Blood Glucose in Type 2 Diabetes Mellitus: A Systematic Review with Meta-analysis

Abstract: Every eleventh adult has diabetes, and every third has prediabetes. Over 95% of diabetics are of type 2. It is well established that diabetes doubles the risk of heart disease and stroke apart from increasing the risk of microvascular complications. Hence, strict glycemic control is necessary. However, it increases the risk of hypoglycemia, especially in patients with longstanding diabetes. Continuous glucose monitors (CGM) use a sensor to continuously measure the glucose levels in the interstitial fluid every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 28 publications
2
76
1
3
Order By: Relevance
“…While persistent daily use of rtCGM is considered essential for intensive insulin management, [1][2][3][9][10][11][12][13][14] clinical trials and recent meta-analyses have reported the value of rtCGM use in individuals with T2D independent of their treatment regimen. [15][16][17][18] The realworld data included in this report add to the growing body of evidence indicating that intermittent rtCGM use with less intensive treatment regimens is associated with significant glycemic improvements, [19][20][21] creates valuable teaching opportunities 22 and is effective in promoting desired self-care behaviors. 20 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 84%
“…While persistent daily use of rtCGM is considered essential for intensive insulin management, [1][2][3][9][10][11][12][13][14] clinical trials and recent meta-analyses have reported the value of rtCGM use in individuals with T2D independent of their treatment regimen. [15][16][17][18] The realworld data included in this report add to the growing body of evidence indicating that intermittent rtCGM use with less intensive treatment regimens is associated with significant glycemic improvements, [19][20][21] creates valuable teaching opportunities 22 and is effective in promoting desired self-care behaviors. 20 Our study has some limitations.…”
Section: Discussionmentioning
confidence: 84%
“…A recent meta-analysis looked exclusively at RCTs specifying individuals with T2D and examined HbA1c as an outcome 38 . They identified five studies that included a total of 382 patients, and found a significant improvement in HbA1c (pooled mean difference of 0.25%) with the use of rtCGM compared to SMBG, providing additional evidence of HbA1c change with rtCGM use.…”
Section: B Improvement In Glucose Control With Rtcgmmentioning
confidence: 99%
“…There are multiple reasons for excluding studies, which are all summarized in Supplementary Table 1 , some of the reasons are systematic review of the application of the technologies, not purely on effectiveness, systematic reviews commissioned by regulatory bodies, which did not provide all evidence, but just a full working summary and others. Finally, we included 32 full systematic reviews and/or meta-analyses for which the research quеstion was clearly defined ( 12 38 , 40 44 ). The included studies were of high quality, predominantly focusing on randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%